FDG PET/CT in Pediatric Neurolymphomatosis. (May 2017) - de Vaugelade, Carole; de Clermont-Gallerande, Henri; Meyer, Marie; My Duyen Tiphaine, Aude; Benjamin, Alice; Ducassou, Stephane; Chateil, Jean-François; Fernandez, Philippe
Abstract : Abstract: An 8-year-old girl presented with back and leg pain and left arm and leg paresis. Lumbar puncture was suggestive of lymphocytic meningitis without identified organism. A second lumbar puncture demonstrated a large number of lymphoid B cells, with positive immunohistochemical staining for CD20 and CD25, proving the diagnosis of neurolymphomatosis. Brain and spine MRI demonstrated involvement of cervical and lumbosacral nerve roots. FDG PET/CT showed multiple bone metastases in addition to nerve involvement. Postchemotherapy FDG PET/CT demonstrated complete metabolic response.